2019
DOI: 10.1038/s41587-019-0325-6
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-stabilized Cas9 nanoparticles and modified repair templates increase genome editing efficiency

Abstract: Versatile and precise genome modifications are needed for a wider range of adoptive cellular therapies 1-5. Here we report two improvements that increase the efficiency of CRISPR-Cas9-Users may view, print, copy, and download text and data-mine the content in such documents, for the purposes of academic research, subject always to the full Conditions of use:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
248
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 231 publications
(255 citation statements)
references
References 17 publications
5
248
2
Order By: Relevance
“…Building on previous work using CRISPR-Cas9 to render primary human immune cells genetically tractable (Hultquist et al, 2019;Hung et al, 2017;Nguyen et al, 2019;Schumann et al, 2015), we have developed a robust, flexible, and high-throughputcompatible platform for the genetic manipulation of primary human myeloid cells. We have optimized cell isolation, culture and CRISPR-Cas9 RNP nucleofection conditions to allow for rapid and inexpensive generation of isogenic modified cells that can then be differentiated and flexibly incorporated into downstream biochemical and phenotypic assays.…”
Section: Discussionmentioning
confidence: 99%
“…Building on previous work using CRISPR-Cas9 to render primary human immune cells genetically tractable (Hultquist et al, 2019;Hung et al, 2017;Nguyen et al, 2019;Schumann et al, 2015), we have developed a robust, flexible, and high-throughputcompatible platform for the genetic manipulation of primary human myeloid cells. We have optimized cell isolation, culture and CRISPR-Cas9 RNP nucleofection conditions to allow for rapid and inexpensive generation of isogenic modified cells that can then be differentiated and flexibly incorporated into downstream biochemical and phenotypic assays.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that CD8+ T cells that occupy these differentiation states would provide a rapid response to nearby reactivated virus because they are localized closer to the sites of HIV reservoir persistence within lymphoid tissues (and, in particular, B cell follicles; (68)(69)(70)). Indeed, studies have suggested that lymphoid tissue from humans and non-human primates that naturally control retroviral infection is enriched for CD8+ T cells that express the TRMassociated protein, CD69 (71,86), as well as CD8+ T cells that express the Tfc-associated chemokine receptor, CXCR5 (72,73). Studies in mice suggest that TCF-1 may directly promote the generation of Tfc (38) but inhibit the formation of TRMs (74).…”
Section: Discussionmentioning
confidence: 99%
“…Our data revealed that electroporation may induce numerous off-target effects on the NK cell repertoire, skew NK cell cytokine production profiles, and deleteriously impact NK cell killing capacity. In these studies, we pre-treated the electroporated NK cells with IL-2, as NK cell activation appears to be required for post-electroporation viability 3539 . Interestingly, the phenotypic changes induced by electroporation were not congruent with the alterations expected to be induced by IL-2 treatment alone.…”
Section: Discussionmentioning
confidence: 99%
“…The most successful non-viral delivery method for primary NK cells is currently electroporation 8,34 . However, electroporated NK cells generally require cytokine stimulation or expansion on genetically-modified feeder cell lines for adequate transfection efficiency and viability post-electroporation 3539 , thereby impeding the study of NK biology by altering cellular physiology and phenotype 40 . We therefore sought to develop and optimize an efficacious and bio-orthogonal transfection strategy for primary NK cells.…”
Section: Introductionmentioning
confidence: 99%